Đang tải thanh công cụ tìm kiếm ...

Giải các phương trình:

Giải các phương trình:

a) \(2{x^3} + 6{x^2} = {x^2} + 3x;\)

b) \(\left( {3x - 1} \right)\left( {{x^2} + 2} \right) = \left( {3x - 1} \right)\left( {7x - 10} \right)\)

Hướng dẫn làm bài:

a) \(2{x^3} + 6{x^2} = {x^2} + 3x\)

⇔\(2{x^2}\left( {x + 3} \right) = x\left( {x + 3} \right)\)

⇔\(2{x^2}\left( {x + 3} \right) - x\left( {x + 3} \right) = 0\)

⇔\(\left[ {\matrix{{x = 0} \cr {x + 3 = 0} \cr {2x - 1 = 0} \cr} \Leftrightarrow \left[ {\matrix{{x = 0} \cr {x = - 3} \cr {x = {1 \over 2}} \cr} } \right.} \right.\)

Vậy tập hợp nghiệm \(S = \left\{ {0; - 3;{1 \over 2}} \right\}\)

b) \(\left( {3x - 1} \right)\left( {{x^2} + 2} \right) = \left( {3x - 1} \right)\left( {7x - 10} \right)\)

⇔\(\left( {3x - 1} \right)\left( {{x^2} + 2} \right) - \left( {3x - 1} \right)\left( {7x - 10} \right) = 0\)

⇔\(\left( {3x - 1} \right)\left( {{x^2} - 7x + 12} \right) = 0\)

⇔\(\left( {3x - 1} \right)\left( {{x^2} - 3x - 4x + 12} \right) = 0\)

⇔\(\left( {3x - 1} \right)\left[ {\left( {{x^2} - 3x} \right) - \left( {4x - 12} \right)} \right] = 0\)

⇔\(\left( {3x - 1} \right)\left[ {x\left( {x - 3} \right) - 4\left( {x - 3} \right)} \right] = 0\)

⇔\(\left( {3x - 1} \right)\left( {x - 3} \right)\left( {x - 4} \right) = 0\)

⇔\(\left[ {\matrix{{3x - 1 = 0} \cr {x - 3 = 0} \cr {x - 4 = 0} \cr} \Leftrightarrow \left[ {\matrix{{x = {1 \over 3}} \cr {x = 3} \cr {x = 4} \cr} } \right.} \right.\)

Vậy tập hợp nghiệm \(S = \left\{ {{1 \over 3};3;4} \right\}\)